Age-dependent modulation of motor network connectivity for skill acquisition, consolidation and interlimb transfer after motor practice. Issue 8 (August 2021) - Veldman, M.P.; Maurits, N.M.; Mantini, D.; Hortobágyi, T.
Highlights: Skill acquisition and consolidation, but not interlimb transfer, are intact in older adults. Unilateral practice increases ipsilateral primary motor cortex (M1)-related coherence in older adults. Motor practice modulates the relationship between M1-related coherence and learning in older adults. Abstract: Objective: Age-related differences in neural strategies for motor learning are not fully understood. We determined the effects of age on the relationship between motor network connectivity and motor skill acquisition, consolidation, and interlimb transfer using dynamic imaging of coherent sources. Methods: Healthy younger ( n  = 24, 18–24 y) and older ( n  = 24, 65–87 y) adults unilaterally practiced a visuomotor task and resting-state electroencephalographic data was acquired before and after practice as well as at retention. Results: The results showed that right-hand skill acquisition and consolidation did not differ between age groups. However, age affected the ability to transfer the newly acquired motor skill to the non-practiced limb. Moreover, strengthened left- and right-primary motor cortex-related beta connectivity was negatively and positively associated with right-hand skill acquisition and left-hand skill consolidation in older adults, respectively. Conclusion: Age-dependent modulations of bilateral resting-state motor network connectivity indicate age-specific strategies for the acquisition, consolidation, and interlimb transfer of novel motor tasks. Significance: The present results provide insights into the mechanisms underlying motor learning that are important for the development of interventions for patients with unilateral injuries.